2021
DOI: 10.3390/biom11081131
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of Single-Domain Antibodies through the Blood–Brain Barrier

Abstract: Single-domain antibodies derive from the heavy-chain-only antibodies of Camelidae (camel, dromedary, llama, alpaca, vicuñas, and guananos; i.e., nanobodies) and cartilaginous fishes (i.e., VNARs). Their small size, antigen specificity, plasticity, and potential to recognize unique conformational epitopes represent a diagnostic and therapeutic opportunity for many central nervous system (CNS) pathologies. However, the blood–brain barrier (BBB) poses a challenge for their delivery into the brain parenchyma. Neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 179 publications
(245 reference statements)
0
36
0
Order By: Relevance
“…Several drug delivery strategies have been introduced to cross the BBB: a paracellular route or passive diffusion by disruption of the BBB, a transcellular route by enhancing transcytosis using molecular BBB shuttles or direct delivery bypassing the BBB with intrathecal, intraventricular or intranasal delivery [ 143 , 144 , 145 ]. While nanobodies have been often discussed in relation to crossing the BBB, the number of experimental validations is rather low.…”
Section: Cns Drug Delivery With Full-length Igg Scfv and Sdabmentioning
confidence: 99%
“…Several drug delivery strategies have been introduced to cross the BBB: a paracellular route or passive diffusion by disruption of the BBB, a transcellular route by enhancing transcytosis using molecular BBB shuttles or direct delivery bypassing the BBB with intrathecal, intraventricular or intranasal delivery [ 143 , 144 , 145 ]. While nanobodies have been often discussed in relation to crossing the BBB, the number of experimental validations is rather low.…”
Section: Cns Drug Delivery With Full-length Igg Scfv and Sdabmentioning
confidence: 99%
“…Various molecular mechanisms for the transportation of nanobodies through the Blood–Brain Barrier (BBB) have been extensively described and include adsorptive and receptor-mediated transcytosis, somatic gene transfer, and the use of carriers or shuttles such as cell-penetrating peptides, extracellular vesicles, liposomes, and nanoparticles as well as device-based and physicochemical disruption of the BBB [ 143 , 144 , 145 , 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of nanobody-based radiotracers for the non-invasive diagnosis of glioblastoma by immuno-PET may also involve some potential challenges. First, suboptimal imaging of glioblastoma may be achieved due to the low penetration of nanobodies through the BBB [ 184 ], although some nanobodies have shown their potential to access the brain parenchyma [ 143 ]. Second, the administration of nanobodies with theragnostic potential may elicit immunogenic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their small size, not surprisingly, a number of teams have recently studied whether Nbs can cross the BBB and whether they could be used for the treatment of brain diseases. The results are very encouraging and have shown that Nbs can reach the brain via the BBB either directly, via receptor-mediated transcytosis, or indirectly, using, for example, various forms of carriers, including nanoparticles or liposomes [ 141 , 142 ]. We also better understand why some Nbs are more efficient at crossing the BBB.…”
Section: Approaches For Targeting and Delivery Of Galectinsmentioning
confidence: 99%